Association of sleep characteristics and night shift work with self-reported diagnosis of polycystic ovary syndrome: a questionnaire-based cross-sectional study. Issue 1 (28th February 2023) - Shao, Shu-Yi; Zhao, Huan-Qiang; Lu, Zhi-Ying; Lei, Xiao-Hong; Zhang, Ying
Abstract : Objective: To examine the association between sleep characteristics and night shift work and the risk of polycystic ovary syndrome (PCOS) in Chinese women and to investigate their relationship with infertility in PCOS. Methods: From March 21, 2021 to April 31, 2021, 3927 Chinese women with or without PCOS were recruited online. All participants completed WeChat-based electronic questionnaires. Sleep characteristics were measured using the Pittsburgh sleep quality index. Results: A total of 2871 women were included in the final analysis. Sleep duration (odds ratio [OR], 0.857; 95% confidence interval [CI], 0.763–0.963), sleep midpoint (OR, 1.142; 95% CI, 1.049–1.244), sleep disturbance (OR, 1.320; 95% CI, 0.957–1.146), daytime dysfunction (OR, 1.136; 95% CI, 1.030–1.253), and night shift work (OR, 1.628; 95% CI, 1.264–2.097) were associated with a higher risk of PCOS. After adjusting for confounders, including age, body mass index, smoking status, and coffee and tea drinking status, sleep disturbance (OR, 1.314; 95% CI, 1.111–1.555), daytime dysfunction (OR, 1.143; 95% CI, 1.034–1.264), and night shift work (OR, 1.800; 95% CI, 1.388–2.333) remained associated. In addition, sleep disturbance (OR, 1.887; 95% CI, 1.400–2.542) and subjective sleep quality (OR, 1.299; 95% CI, 1.037–1.627) were associated with infertility in women with PCOS, and sleep disturbance (OR, 1.750; 95% CI, 1.281–2.390) remained significant after adjusting for confounders. Conclusions: Sleep disturbance, daytime dysfunction, and night shift work are significantly associated with PCOS. Screening for sleep disturbances and providing appropriate treatment could be potential strategies for managing PCOS and its long-term complications.